Sensitivity of UK butterflies to local climatic extremes: which life stages are most at risk?. (31st October 2016) - McDermott Long, Osgur; Warren, Rachel; Price, Jeff; Brereton, Tom M.; Botham, Marc S.; Franco, Aldina M. A.
Summary: There is growing recognition as to the importance of extreme climatic events (ECEs) in determining changes in species populations. In fact, it is often the extent of climate variability that determines a population's ability to persist at a given site. This study examined the impact of ECEs on the resident UK butterfly species ( n = 41) over a 37‐year period. The study investigated the sensitivity of butterflies to four extremes (drought, extreme precipitation, extreme heat and extreme cold), identified at the site level, across each species' life stages. Variations in the vulnerability of butterflies at the site level were also compared based on three life‐history traits (voltinism, habitat requirement and range). This is the first study to examine the effects of ECEs at the site level across all life stages of a butterfly, identifying sensitive life stages and unravelling the role life‐history traits play in species sensitivity to ECEs. Butterfly population changes were found to be primarily driven by temperature extremes. Extreme heat was detrimental during overwintering periods and beneficial during adult periods and extreme cold had opposite impacts on both of these life stages. Previously undocumented detrimental effects were identified for extreme precipitation during the pupal life stage for univoltine species. Generalists were found to have significantly more negative associations with ECEs than specialists. With future projections of warmer, wetter winters and more severe weather events, UK butterflies could come under severe pressure given the findings of this study. Abstract : This paper tackles a previously understudied field, addressing the impacts of extreme weather on biodiversity specifically butterflies in this study. It has used novel and dynamic approaches to identify extreme weather events which vary according to the life stage for each species and has identified some very interesting results.